2002
DOI: 10.1074/jbc.m206184200
|View full text |Cite
|
Sign up to set email alerts
|

A Role for G1/S Cyclin-dependent Protein Kinases in the Apoptotic Response to Ionizing Radiation

Abstract: In Xenopus development the mid-blastula transition (MBT) marks a dramatic change in response of the embryo to ionizing radiation. Whereas inhibition of cyclin D1-Cdk4 and cyclin A2-Cdk2 by p27Xic1 has been linked to cell cycle arrest and prevention of apoptosis in embryos irradiated post-MBT, distinct roles for these complexes during apoptosis are evident in embryos irradiated pre-MBT. Cyclin A2 is cleaved by caspases to generate a truncated complex termed ⌬N-cyclin A2-Cdk2, which is kinase active, not inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 58 publications
(38 reference statements)
0
36
0
Order By: Relevance
“…2D). Cleavage of cyclin A to a nondegradable fragment (33) has been reported to play a role in apoptosis (34). Cleavage of cyclin-dependent kinase inhibitors p27 and p21 in apoptotic cells has also been reported (35).…”
Section: Ras-induced Apoptosis Ismentioning
confidence: 99%
“…2D). Cleavage of cyclin A to a nondegradable fragment (33) has been reported to play a role in apoptosis (34). Cleavage of cyclin-dependent kinase inhibitors p27 and p21 in apoptotic cells has also been reported (35).…”
Section: Ras-induced Apoptosis Ismentioning
confidence: 99%
“…Levels and cleavage products of various cyclins have been implicated in apoptosis induction (Finkielstein et al, 2002;Mazumder et al, 2002). Also, accumulation of CDKI P27 Kip1 and cyclin E in mice deficient in its E3 ligase Skp2 results in increased spontaneous apoptosis (Nakayama et al, 2000), and the level of Skp2 in gastric carcinomas modulates the phenotype of the cancer, presumably by affecting P27 expression (Masuda et al, 2002).…”
Section: Cell Deathmentioning
confidence: 99%
“…Overexpression of cyclin D1 has been reported to radiosensitize cancer cells, a finding that was ascribed to effects on the G2/M transition (Coco Martin et al, 1999). Caspase cleavage of both cyclin D1-CDK4 and cyclin A-CDK2 has been suggested to promote apoptosis in embryos following ionizing radiation exposure (Finkielstein et al, 2002), indicating that cell cycle arrest may be linked to apoptosis. Links between cyclin D and transcription have also been suggested (Coqueret, 2002).…”
Section: Cell Cyclementioning
confidence: 99%
“…Cdk4 has not been described as a caspase 3 substrate, and we were unable to identify any potential cleavage sites. On the other hand, cyclin D1 from Xenopus laevis is cleaved by caspase 3 at a DEVD 278 site (18). However, we found that human cyclin D1 (which has the sequence EEVD) was not a substrate for caspase 3 under conditions in which known substrates were efficiently cleaved (data not shown).…”
Section: The C Terminus Of Rb Is Required For the Phosphorylation Of mentioning
confidence: 43%